The use of GIS in the analysis of existing condition of spatial distribution of wire communications network in the city of Baghdad - زايد المالكي, ندى قاسم; جعفر الحسيني, حسن عبدالحسين (Journal of Planner and Development, 2011)
The increasing efficiency of the telecommunications network in the city contributes to the increase in spatial interaction between activities (to influence and mutual influence) This study is based on the idea that the upgrading of telephone services provided to citizens are done exclusively through the growth and development of all levels of the service using advanced technologies to know the problems and appropriate solutions in short time and less cost. Thus, crystallized the objectives of the study which was built for the importance of GIS in the planning of services in general, and infrastructure services, in particular, including telephone services, which is represent a point of contact between individuals on the one hand and cities with each other on the other. Study seeks to clarify the most important variables affecting and involved in the installation of this service (telecommunications network) and the review of the most important problems and constraints faced the telephone service in the city. The study included theoretical coverage of the effect of telecommunications in the form of the city. The study based on the planning standards and constraints of services, including telecommunications network as well as the study showed the role of GIS in the study of urban planning and appropriate spatial distribution of the telecommunicationsservice. The practical side of study addresses the reality of the spatial distribution of the telecommunications network in the city of Baghdad and state the spatial imbalance in all sectors of the city. The spatial allocation for the telecommunications network in the city depends on the standards affected by both the density of family and the distance and study of those standards. The research reached to suggest suitable locations within the sectors of the city of Baghdad to handle this lake according to the density of family after determining the scope of telephone capacity extension and working telephone for each exchanger using Geographic                                                                                                                     Information Systems GIS .